Empowering Future Teachers: The Role of Student Organizations in Enhancing Public Speaking and Teaching Skills - Zahra Alfi; Nur Amalia (Universitas Sebelas Maret, 2024)
Recognizing the pivotal role of teachers in shaping education, extensive research has been conducted to assess their effectiveness. Among the prominent challenges faced by many educators is mastering public speaking, a crucial skill for effective classroom instruction. This study delves into whether participation in student groups can augment aspiring elementary school teachers' public speaking and teaching competencies while emphasizing the significance of public speaking skills within the teaching profession. Employing descriptive qualitative methods such as interviews, observations, and document analysis, the research elucidates the profound impact of public speaking proficiency on teaching effectiveness. The study encompasses four key stages: preparation, implementation, analysis, and reporting. Twelve students participated as respondents, focusing on those actively engaged in group activities. Additionally, six lecturers from the Primary School Teacher Education Study Program, Muhammadiyah University of Surakarta, knowledgeable about the fundamental skill requirements for aspiring teachers and the program director, served as supplementary subjects. The findings suggest that engagement in student groups can significantly enhance aspiring teachers' public speaking skills, thereby better equipping them for successful careers in education.